UJI AKTIVITAS KATALIS Ni-Mo/ZEOLIT PADA REAKSI HIDRORENGKAH FRAKSI SAMPAH PLASTIK (POLIETILEN) (Universitas Negeri Semarang, 2012)
The catalytic activity test of Ni-Mo/Zeolite catalyst in the hydrocracking reaction of polyethylene (HDPE) waste fraction have been investigated. The purpose of this study was to determine the catalytic activity of Ni-Mo/ZA on hydrocracking reactions of polyethylene waste. This research studied the effect of the mass ratio of catalyst / feed and reaction temperature. The catalysts were prepared by the following procedure: activation by acid and salt (1% HF, 6 M HCl, and 1 N NH4Cl), calcination with N2, oxidation with O2, and finally reduction with H2. Further Ni and Mo was impregnated into zeolite with the order: Mo first, then Ni (ratio of Ni : Mo is 1:2). Characterization of catalysts include the determination of surface area by BET method, the acidity of catalyst by gravimetric method, and the distribution of the bimetallic Ni-Mo metal by Atomic Absorption Spectrophotometer (AAS) respectively. Polyethylene plastic waste first treat by the pyrolysis method at a temperature of 550oC while flowing N2. Hydrocracking process was operated in a flow- fixed bed reactor by varying the mass ratio of catalyst / feed 1 : 4, 2 : 4, 3 : 4, and operating temperature at 350oC, 400oC, 450oC, 500oC, 550oC for 2 hours. The liquid product of hydrocracking process was analyzed by GC and GC-MS. Analysis of data showed that the greatest catalytic activity of Ni-Mo/ZA at a temperature 500oC resulting a conversion of 1.334%. GC-MS analysis showed that the liquid hydrocracking products at the optimum temperature has a chemical composition consisting of ethanal, 2-propanone and 3-Methyl-2-pentanone.